AVENIR Baseline Study - Muriithi, Cyrus K (2023)
This baseline survey data was collected in Senegal in the regions of Sedhiou and Tambacounda in 2020. It's part of an agricultural development project aimed at improving the well-being and resilience of farming households. (2020-12-01)